Spatial Analysis of Narcotics Abuse Based on Knowledge, Socio-Demographics, Social Environment, and Swamp Land - Rahman, Abdul; Rejo, Amin; Purnama, Dadang Hikmah; Zuhir, Mada Apriadi (Journal of Ecohumanism, 2024)
Narcotics abuse is a serious issue that affects public health and social stability, making it crucial to understand the factors contributing to this phenomenon. This study aims to analyze narcotics abuse based on knowledge, socio-demographics, social environment, and swamp land characteristics. The research was conducted in Palembang, the capital of South Sumatra Province, which has diverse geographical and socio-economic characteristics. Palembang is one of Indonesia's major cities with a relatively high population density, featuring various areas interconnected by river networks and swamp lands. The sample consists of 100 narcotics-related cases. Using spatial analysis methods, the respondent data were grouped into low, medium, and high categories for each variable. The results indicate that areas with low knowledge and education, as well as a negative social environment, have higher rates of narcotics abuse. Conversely, areas with balanced characteristics in these aspects tend to have a lower risk of abuse. Additionally, swamp land characteristics also contribute to the level of narcotics abuse. These findings highlight the need for targeted interventions, including educational programs and community strengthening, to reduce the risk of narcotics abuse. This study provides important insights for developing more effective policies in combating narcotics abuse in society.